2001
DOI: 10.1054/bjoc.2001.1703
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on gynaecological effects of two antioestrogens tamoxifen and toremifene in postmenopausal women

Abstract: To assess and compare the gynaecological consequences of the use of 2 antioestrogens we examined 167 postmenopausal breast cancer patients before and during the use of either tamoxifen (20 mg/day, n = 84) or toremifene (40 mg/day, n = 83) as an adjuvant treatment of stage II–III breast cancer. Detailed interview concerning menopausal symptoms, pelvic examination including transvaginal sonography (TVS) and collection of endometrial sample were performed at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…A 3-year study specifically designed to compare the gynecological effects of toremifene 40 mg and tamoxifen 20 mg in 167 postmenopausal breast cancer patients showed that the incidence of proliferative endometrium was increased to a significantly (P < 0.0001) lesser extent by toremifene (from 20.0% to 32.2%) than by tamoxifen (from 20.4% to 46.8%) [60] .…”
Section: Long Term Safetymentioning
confidence: 99%
“…A 3-year study specifically designed to compare the gynecological effects of toremifene 40 mg and tamoxifen 20 mg in 167 postmenopausal breast cancer patients showed that the incidence of proliferative endometrium was increased to a significantly (P < 0.0001) lesser extent by toremifene (from 20.0% to 32.2%) than by tamoxifen (from 20.4% to 46.8%) [60] .…”
Section: Long Term Safetymentioning
confidence: 99%
“…Disappointing efficacy data for both droloxifene and idoxifene when compared with tamoxifen or when used in tamoxifen-resistant disease have led to their development being halted. Toremifene (chloro-tamoxifen), which has similar efficacy but fewer agonist properties compared with tamoxifen (Marttunen et al 1998(Marttunen et al , 2001, remains in clinical development in the breast cancer prevention setting.…”
Section: Introductionmentioning
confidence: 99%
“…MB Marttunen et al suggested that at least in the first 2-3 years, toremifene treatment does not increase the risk of endometrial cancer. 12 According to Ha et al, 8 the majority of uterine cancers developed after more than 1 year of treatment, and the annual hazard rate for endometrial cancer was 1.0 per 1,000 patient treatment years. Adenosarcoma is a very rare uterine malignancy detected in this patient on toremifene therapy who has no risk factors for uterine malignancy other than old age.…”
Section: Discussionmentioning
confidence: 99%